Rola kredytowych transakcji terminowych w procesie zarządzania finansami przedsiębiorstw - Strycharczyk, Agnieszka (Credit Derivatives in the Process of Corporate Finance Management, 2006)
The development of globalization, new technologies and new markets eventually made financial institution seek for more advanced credit risk reduction techniques which resulted in the creation of the first credit derivatives - simple, single name Credit Default Swaps. Credit derivatives are over-the-counter financial instruments that enable parties to isolate specific aspects of credit risk from an underlying instrument and transfer that risk from one party to another. With the appearance of credit derivatives, credit risk management of loan portfolio does not mean a strategy of portfolio diversification backed by line limits or sale of positions in the secondary market any more. Credit derivatives also allow to separate the management of credit risk from the asset which generates that risk. Since the first transaction introduced, the market has grown rapidly and become an important tool for banks and other financial institutions to transfer or take on credit risk. Recently in Poland there have been also made significant moves towards standardization of these contracts that among the other credit risk transfer instruments can gain significant meaning.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 579-586